Predation release of Texas horned lizards (Phrynosoma cornutum) living in small towns - Stephen Mirkin; Mary R. Tucker; Dean A. Williams (Ecology and Evolution, 2021)
Abstract Texas horned lizards (Phrynosoma cornutum) have a number of ways to avoid predation, including camouflage, sharp cranial horns, flattening of the body, and the ability to squirt blood from the eyes. These characteristics and their relatively low survival rates in the wild suggest these lizards are under high predation pressure. These lizards have been declining in much of their eastern range due to increased urbanization, agriculture, and loss of prey species. However, they can be still be found in some small south Texas towns where they can reach densities that are much higher (~50 lizards/ha) than in natural areas (~4–10 lizards/ha). We hypothesized that one reason for the high densities observed in these towns may be due to reduced predation pressure. We used model Texas horned lizards to test whether predation levels were lower in two south Texas towns than on a nearby ranch. We constructed models from urethane foam, a material that is ideal for preserving marks left behind by predators. Models (n = 126) and control pieces of foam (n = 21) were left in the field for 9 days in each location in early and late summer and subsequent predation marks were categorized by predator taxa. We observed significantly more predation attempts on the models than on controls and significantly fewer attempts in town (n = 1) compared with the ranch (n = 60). On the ranch, avian predation attempts appear to be common especially when the models did not match the color of the soil. Our results suggest that human‐modified environments that have suitable habitat and food resources may provide a refuge for some prey species like horned lizards from predators.